Extraction of Illegal Dyes from Red Chili Peppers with Cholinium-Based Deep Eutectic Solvents - Shuqiang Zhu; Dongling Liu; Xinyue Zhu; Along Su; Haixia Zhang (Journal of Analytical Methods in Chemistry)
Deep eutectic solvents (DESs) as a new kind of green solvents have been used to extract bioactive compounds but there are few applications in extracting chrysoidine dyes. In this study, we developed an ultrasonic-assisted extraction method with choline chloride/hydrogen bond donor (ChCl/HBD) DES for the extraction of chrysoidine G (COG), astrazon orange G (AOG), and astrazon orange R (AOR) in food samples. Some experimental parameters, such as extraction time, raw material/solvent ratio, and temperature, were evaluated and optimized as follows: the ratio of ChCl/HBD, 1 : 2 (v/v); the ratio of sample/DES, 1 : 10 (g/mL); extraction time, 20 min; extraction temperature, 50°C. Under the optimized conditions, the limits of detection (μg/mL) were 0.10 for COG and 0.06 for AOG and AOR. The relative standard deviations were in the range of 1.2–2.1%. The recoveries of the three dyes were in the range of 80.2–105.0%. By comparing with other commonly used solvents for extracting chrysoidine dyes, the advantages of DESs proved them to be potential extraction solvents for chrysoidine G, astrazon orange G, and astrazon orange R in foods.